Sistem Pendukung Keputusan Seleksi Penerimaan Karyawan Baru Di PT. Bank Rakyat Indonesia Cabang Lubuklinggau Mengunkan Metode Weighted Product Berbasis Web - Dimas Ade Prasetyo; Joni Karman; Lukman Hakim (LPPM STIKOM Tunas Bangsa, 2024)
One of the success factors for a company is its employees, therefore companies must have quality human resources, in order to build the company in a better direction. Negligence in selecting human resources will cause problems and can result in business failure. To obtain competent human resources, and in accordance with the required classification, proper selection is needed in recruitment. In order for the recruitment process to be objective, an appropriate method is needed for recruiting employees. The Weighted Product method can be used in decision making. In the recruitment process five criteria are used, namely recent education, suitability of major, age, work experience, work experience. In this case, prospective employees are compared with one another so as to provide an output of priority intensity values which results in a system that provides an assessment of each employee. This decision support system helps assess each employee, make changes to criteria, and change weight values. This is useful for facilitating decision making related to employee selection issues, so that employees who are most worthy of being accepted into the company will be obtained.